Respectful Disposition After Miscarriage: Clinical Practice Recommendations. Issue 1 (January 2018) - Levang, Elizabeth; Limbo, Rana; Ziegler, Tammara Ruiz
Abstract : Abstract: Compassionate clinical practice guidelines for healthcare providers for respectful disposition after miscarriage are presented. When woven into the whole of a clinician's practice, these guidelines provide the framework for giving women and their families the care they want and deserve when experiencing miscarriage. Relying on theoretical concepts of personhood, place, and protection, care providers can assess the unique meaning a woman assigns to her early pregnancy loss and offer interventions that embrace the concept of respectful disposition. Respectful methods of disposition involve a continuum of care that shows respect for remains and relies on person-, family-, and culture-centered nursing care. Policies, practices, and perspectives that flow from respectful disposition have women and families at their core and flexibility to cocreate care. This involves courage and competence. Several states have enacted fetal disposition laws, but these mandates are of questionable benefit because the expertise of healthcare leaders, nurses, physicians, chaplains, and other stakeholders must be involved in this sensitive and important area of care. Compassionate care cannot be legislated. We offer a practical approach to respectful disposition, including how to handle and prepare remains and examples of burial and memorial services, which will give clinicians the ability to respond empathetically and respectfully to the heart-rending plea of a woman who asks, "Where is my baby?" Abstract : Respectful disposition after miscarriage is a continuum of care that includes procedures for the safe and respectful handling of all fetal remains, accurate and sensitive patient information, disposition options, and person-, family-, and culture-centered nursing care. Compassionate clinical practice guidelines for healthcare providers for respectful disposition after miscarriage are presented.